Mối quan hệ giữa quản trị tồn kho, hiệu suất chuỗi cung ứng và hiệu quả tài chính tại các doanh nghiệp sản xuất trên địa bàn TP. Hồ Chí Minh - Nguyễn Văn , Ít (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This research examines the relationship between inventory management, supply chain performance, and financial performance. Surveyed data was collected from 369 managers working at manufacturing enterprises in Ho Chi Minh City. The result of structural equation modeling showed that the supply chain performance has a strongest positive impact on the financial performance. Then, the inventory management has the second strong positive impact on the supply chain performance and finally, the inventory management has the lowest positive impact on the financial performance. Based on the findings, some implications are drawn to help that the managers of manufacturing enterprises improve inventory management, supply chain performance, thereby contributing to increasing financial performance.
Keywords: Manufacturing enterprises; Financial performance; Supply chain performance; Inventory management